Building health literacy system capacity: a framework for health literate systems. (12th December 2021) - Sørensen, Kristine; Levin-Zamir, Diane; Duong, Tuyen V; Okan, Orkan; Brasil, Virginia Visconde; Nutbeam, Don
Summary: The human and social implications of poor health literacy are substantial and wide-ranging. Health literacy represents the personal competencies and organizational structures, resources and commitment that enable people to access, understand, appraise and use information and services in ways that promote and maintain good health. A large-scale societal improvement of health literacy will require political buy-in and a systematic approach to the development of health literacy capacity at all levels. This article builds the case for enhancing health literacy system capacity and presents a framework with eight action areas to accommodate the structural transformation needed at micro, meso and macro levels, including a health literate workforce, health literate organization, health literacy data governance, people-centred services and environments based on user engagement, health literacy leadership, health literacy investments and financial resources, health literacy-informed technology and innovation, and partnerships and inter-sectoral collaboration. Investment in the health literacy system capacity ensures an imperative and systemic effort and transformation which can be multiplied and sustained over time and is resilient towards external trends and events, rather than relying on organizational and individual behavioural change alone. Nevertheless, challenges still remain, e.g. to specify the economic benefits more in detail, develop and integrate data governance systems and go beyond healthcare to engage in health literacy system capacity within a wider societal context. Lay Summary: Health literacy represents the personal competencies and organizational structures and resources enabling people to access, understand, appraise and use information and services in ways that promote and maintain good health. To meet the needs related to impact of poor health literacy, this article introduces a framework for the development of health literacy system capacity with eight action areas including the development of a health literate workforce, health literate organization, health literacy data governance, people-centred services and environments based on user engagement, health literacy leadership, health literacy investments and financial resources, health literacy-informed technology and innovation, and partnerships and inter-sectoral collaboration. Investment in health literacy system capacity ensures a future-proof effort that can be multiplied and sustained over time, rather than relying on organizational or individual behavioural change alone.